Hubungan Paritas dengan Kepatuhan Melakukan Kunjungan Ulang KB Suntik Pada Akseptor Suntik di BPM Rizka Devi Savitri di Desa Bondoyudo Sukodono Lumajang - Lilis Setianingsih; Mutmainnah Zakiyyah; Nova Hikmawati (NHM PRESS, 2023)
There are many factors that have reduced acceptors of injecting family planning to make visits including parity, husband support, education, occupation and age of acceptors. This study aimed to determine the correlation between parity and adherence to repeat injection contraception. The method was a correlational research method using a cross sectional approach to data collection techniques using random sampling techniques. Based on the result of the study we were able to get a total of 72 respondents. It was found that the majority of respondents who adhered to repeat injection contraceptive visits were multiparas, namely 46 respondents (68,89%).The research analysis uses the chi square test and SPSS, This research found P value = 0.000. From the result of one study we found a relationship between parity and adherence to repeat injection KB visits with P Value = 0.000.